PENGENALAN ASSESSMENT FOR LEARNING (AfL) BAGI GURU - Nunung Sobarningsih; Tika Karlina Rachmawati; Riva Lesta Ariany (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2018)
ABSTRACTThe curriculum used in education today is the 2013 curriculum. The emphasis of assessment within the 2013 curriculum is authentic assessment. Summative assessment and formative assessment are part of the authentic assessment. Summative assessment has been widely applied by teachers but it is still rare for teachers to apply formative assessments. In formative assessment, the teacher assesses during the learning process and the teacher still has difficulty in doing assessment during the learning process. To find alternative solutions then held training on formative assessment such as assessment by using Assessment for Learning. The purpose of community service is to provide insight to teachers about Assessment for Learning (AfL) that can be developed and utilized in accordance with the competence to be achieved. Target community in dedication to this community is the teachers MTs Negeri 2 Bandung, amounting to 50 people. This activity was held on October 19, 2016, which was held in the hall of MTs Negeri 2 Bandung City, teacher assistance implemented AfL 1 on October 25, 2016 in class VIII B and VIII G, while teacher assistance implemented AfL 2 on October 26, 2016 in class VIII B and VIII F. From the evaluation results obtained the results of activities of service to these communities such as increasing the knowledge of teachers in conducting formative assessment by Assessment for Learning. With the holding of teacher assistance in the classroom then the teacher will understand the application of Assessment for Learning in the learning process. This devotion works smoothly because of the support from various parties and the participation of participants who are quite enthusiastic and actively participate in this training. These devotional activities should be performed on broader goals and can be developed with other assessments. Thus, it is hoped that in the future they will be able to assist teachers in developing the assessment especially formative assessment in the learning process.Keywords: assessment, formative assessment, Assessment for Learning (AfL)Â ABSTRAKKurikulum yang digunakan dalam pendidikan sekarang ini adalah kurikulum 2013. Penekanan penilaian di dalam kurikulum 2013 adalah penilaian autentik. Penilaian sumatif dan penilaian formatif merupakan bagian dari penilaian autentik. Penilaian sumatif sudah banyak diterapkan oleh guru tetapi masih jarang guru yang menerapkan penilaian formatif. Di dalam penilaian formatif, guru melakukan penilaian selama proses pembelajaran dan guru masih kesulitan dalam melakukan assessment selama proses pembelajaran. Untuk mencari alternatif solusinya maka diadakan pelatihan tentang penilaian formatif seperti penilaian dengan menggunakan Assessment for Learning. Tujuan kegiatan pengabdian kepada masyarakat ini adalah memberikan wawasan kepada guru-guru tentang Assessment for Learning (AfL) yang dapat dikembangkan dan dimanfaatkan sesuai dengan kompetensi yang ingin dicapai. Sasaran masyarakat dalam pengabdian kepada masyarakat ini adalah guru-guru MTs Negeri 2 Kota Bandung yang berjumlah 50 orang. Kegiatan ini dilaksanakan pada tanggal 19 Oktober 2016 yang bertempat di aula MTs Negeri 2 Kota Bandung, pendampingan guru menerapkan AfL 1 pada tanggal 25 Oktober 2016 di kelas VIII B dan VIII G, sedangkan pendampingan guru menerapkan AfL 2 pada tanggal 26 Oktober 2016 di kelas VIII B dan VIII F. Dari hasil evaluasi diperoleh hasil dari kegiatan pengabdian kepada masyarakat ini diantaranya adalah meningkatkan pengetahuan guru dalam melakukan penilaian formatif secara Assessment for Learning. Dengan diadakannya pendampingan guru di kelas maka guru akan memahami penerapan Assessment for Learning dalam proses pembelajaran. Kegiatan pengabdian ini berjalan lancar karena mendapatkan dukungan dari berbagai pihak serta partisipasi peserta yang cukup antusias dan berpartisipasi aktif dalam pelatihan ini. Kegiatan pengabdian ini hendaknya dilakukan pada sasaran yang lebih luas dan dapat dikembangkan dengan assessment yang lain. Dengan demikian, diharapkan kelak dapat membantu guru-guru dalam mengembangkan penilaian khusunya penilaian formatif dalam proses pembelajaran.Kata Kunci: penilaian, penilaian formatif, Assessment for Learning (AfL)